Food Product Development / From Concept to the Marketplace - Graf Ernst; Saguy Israel Sam (Addison-Wesley, 1991)
Preface, Consumer Research, Engineering and Manufacturing, Safety and Regulatory Aspects, Optimizing Consumer Product Acceptance and Perceived Sensory Quality, Product Excellence Through Experimental Design, The History and Current Status and Future of Nutritional Food Product Development, The Role of the Flavor Supplier, Protection of Intellectual Property, Food Issues in Food Science and Engineering, Strategies for Global Product Development, Index.
Preface, Consumer Research, Engineering and Manufacturing, Safety and Regulatory Aspects, Optimizing Consumer Product Acceptance and Perceived Sensory Quality, Product Excellence Through Experimental Design, The History and Current Status and Future of Nutritional Food Product Development, The Role of the Flavor Supplier, Protection of Intellectual Property, Food Issues in Food Science and Engineering, Strategies for Global Product Development, Index.